A successful management of children with retroperitoneal abscess due to recurrent renal staghorn calculi - Krisni Subandiyah; Astrid Kristina Kardani; Tita Luthfia Sari (Medical Faculty of Brawijaya University, Indonesia, 2024)
Introduction: A particular kind of urolithiasis known as